Creating a thinking space for the rising stars of Australian urban geography. Issue 2 (3rd April 2019) - Rogers, Dallas; Porter, Libby; Steele, Wendy; Houston, Donna
ABSTRACT: The Institute of Australian Geographers Urban Study Group and Australian Geographer present the first essay in our Leading Insights/Thinking Space partnership. We discuss Dr Natalie Osborne's 2018 essay, flag Dr Marilu Melo's 2019 essay and talk about creating a thinking space for the rising stars of Australian urban geography.